(untitled) (Research, Society and Development, 2025)
Acute kidney injury (AKI) is a common and serious syndrome among critically ill patients. Patients in intensive care units (ICUs) are at particularly high risk of developing AKI due to a combination of multiple risk factors: preexisting comorbidities (such as hypertension, chronic kidney disease, liver failure), use of nephrotoxic drugs, iodinated contrast media, hypoxia, sepsis, hemodynamic instability, and invasive support (mechanical ventilation, vasopressor use). The objective of this article, through a descriptive observational study, is to report the epidemiological profile of patients who initiated renal replacement therapy in the Intensive Care Unit of a hospital in northwestern São Paulo, highlighting the importance of early diagnosis and treatment of reversible causes to reduce potential future complications. This descriptive observational study was conducted through documentary research of direct sources in medical records, with a quantitative approach. In this study, AKI was frequent in the ICU, and risk factors for its development were identified as being over 45 years of age, being more evident among those over 70 years of age, admission creatinine greater than 2.0 mg dL, and the association mainly with systemic arterial hypertension and type 2 diabetes mellitus. Therefore, it is essential that from the hospitalization of all patients, but especially in the intensive care setting, the factors associated with the development of AKI are analyzed, for prevention and adequate management, aiming to avoid unfavorable complications.